THE INFLUENCE OF SERVICE QUALITY TOWARD SALES OF TICKET AND MEMBERSHIP (Case study: Garuda Indonesia Airline) - Setyawati, Agung M. Yuni; Lapian, Joyce; Tasik, Hizkia (Universitas Sam Ratulangi, 2016)
Abstract: Transportation has become one of the most important services for supporting people’s daily activities. One of transportation that exist in the whole world is airplane. Garuda Indonesia as one of airline in Indonesia should be focus on service quality. The aim of this research is to analyze the influence of service quality toward sales of ticket and membership of Garuda Indonesia. The analysis method that used in this research is Time Series Regression. Tangible, reliability, responsiveness, assurance and empathy are the independent variables of this research. While, dependent variables of this research are sales of ticket and membership. The population of this research is airplane in Indonesia and the sample of this research is Garuda Indonesia Airline. The result of this research shows that based on F test, all independent variables (tangible, reliability, responsiveness, assurance and empathy) have simultaneous influence on sales of ticket and membership. While, based on T test the independent variable that influences sales of ticket partially is tangible and independent variables that influence membershippartially are tangible, responsiveness and empathy. Based on time series regression result, independent variable that has significant value less than 5% (<0.05) influence onsales of ticket and membership are tangible, reliability and assurance. Keywords: Service Quality, Sales of Ticket, Membership, Time series Regression